Government House, Trinidad - (:unkn) unknown (Davidson and Todd, Ltd., Trinidad, 2009)
A picture of a walkway leading to the Government House main building with a fountain at the centre, tropical plants of the Botanical Gardens line the walkway.
Colour; Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Public buildings; President's House, The; Botanical gardens; Fountains